Ethnobotanical survey: A comprehensive review of medicinal plants used in treatment of gastro intestinal diseases in Kano state, Nigeria. - Asmau Nna Sulaiman; Auwalu Halliru Arzai; Dalha Wada Taura (Elsevier, 2022)
Background: This work provides the ethnobotanical data concerning the traditional use of medicinal plants in Kano State- Nigeria and its uses for the treatment of gastrointestinal disease which has been poorly investigated. The aim of this study was to review the actual knowledge about the medicinal plants used to treat gastrointestinal diseases by traditional medical practitioners living in Kano metropolis. The objectives were to determine the local (Hausa) and scientific names of the plants used in the treatment of gastrointestinal diseases in Kano State, Nigeria; to document and analyse the traditional and ethnobotanical knowledge inherited by traditional medical practitioners in Kano State- Nigeria. Method: The ethnobotanical data was collected from 30 traditional medical practitioners, 5 each from each Local Government Area making up the core Kano metropolis (Dala, Fagge, Tarauni, Kano Municipal, Gwale and Nassarawa). By means of a structured questionnaire focusing on the local (Hausa) names of the medicinal plants, their medicinal uses, the plant parts used, methods of preparation and route of administration to patients. Results: The survey identified a total of 33 plant species belonging to 24 families. The Moraceae family was the most commonly used plant family representing 17.4% of all the medicinal plants species recorded in this study. The plant parts most frequently used were the leaves (47.8 %), followed by the bark/stem (34.8 %), roots (10.9 %), whole plant (4.3 %) and the seeds (2.2 %). Most of the traditional medical practitioners obtained their extracts by decoction of the medicinal plants. The most often recurring gastrointestinal disease treated by the practitioners was stomach ache (36.5 %), followed by diarrhoea (30.8 %), and dysentery (19.2 %) using one or more of the medicinal plants reported in this study for preparing such treatments. The three (3) most frequently used plants according to this study were: Bridelia ferruginea (90.0 %), Psidium guajava (90.0 %) and Khaya senegalensis (83.3 %). The survey revealed that the bark of both Bridelia ferruginea and Khaya senegalensis were the parts used for the herbal preparation while the leaves of Psidium guajava were used. The main method of preparation was decoction and was administered orally. Conclusion: : The traditional medical practitioners in Kano metropolis possess a wealth of information on medicinal plants and their applications. This ethnobotanical survey can help scientists and researchers in identifying those plants with medicinal properties that may be useful in the development of new drugs.